Making the dream a reality: how are we going to end fistula within a generation? - Anastasi, Erin; Asiamah, Bridget (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To provide a global overview on progress, successes, challenges/lessons learned, and the way forward towards the UN global vision of ending fistula within a generation. Methods: This interactive presentation will feature highlights of the 2018 United Nations Secretary-General's report on "Intensifying efforts to end obstetric fistula within a generation" and the subsequent United Nations General Assembly Resolution A/RES/71/169. Results: Key elements in the Report include linking the call to end fistula within a generation with the achievement of the Sustainable Development Goals (SDGs); integrating fistula with global efforts to achieve universal access to emergency/essential surgery; addressing root causes of fistula; and calling for UNFPA/Campaign to End Fistula to lead development of a new global road map to end fistula within a generation. Conclusions: To succeed in ending fistula within a generation, we must galvanize momentum and mobilize the international community to invest and act upon key recommendations of the 2018 Secretary General’s Report on fistula. These include: strengthening health systems; implementing and monitoring cost national strategies for eliminating fistula; including fistula into national SDGs implementation plans; strengthening national task forces for fistula; securing significantly increased, predictable, sustained, and adequate financial support; strengthening awareness-raising and advocacy; and improving research, data collection, monitoring and evaluation to end fistula and make the “invisible”, visible.